Are livelihoods of slum dwellers sustainable and secure in developing economies? Evidences from Lucknow, Uttar Pradesh in India - Sanatan Nayak; Surendra Singh Jatav (Heliyon, 2023)
Objectives: We adopted the Sustainable Livelihood Security (SLS) approach to assess the living conditions of slum dwellers in Lucknow, Uttar Pradesh, India. Keeping the urban poor at the centre, we attempted to bring out the multidimensional nature of poverty and explored various aspects of the livelihood of slum dwellers. Methods: We surveyed 900 households from both notified and non-notified slums of Lucknow city to construct the SLS index, keeping the social, economic, infrastructural, health, and micro-environmental aspects of slum dwellers in the background. We collected data based on the household approach of the UN and the neighbourhood approach of the Government of India and aggregated the weighted index values under various sub-components to construct a composite index. Results: The results suggested that the index values were low for both types of slum dwellers in Lucknow city specifically in the economic, infrastructural, and micro-environmental aspects. The results also showed that ‘non-notified slum dwellers’ were much more deficient in all the dimensions compared to their ‘notified’ counterparts. The livelihood condition of the marginalized households (backward castes and minorities) was especially precarious and vulnerable. Conclusion: The findings reveal the existence of a high level of informality of livelihood of the urban poor in terms of housing, employment, health, and other basic amenities, and demonstrate that their livelihood condition is characterized by a low assets base, and poor strategies to overcome exigencies and risks. Recommendations: This paper recommends enactment of an urban employment guarantee act, conducting of sabhas (meetings) at the ward level on a regular basis to promote awareness, and notification of non-notified slums to notified slums on regular basis for the overall development of slum dwellers.